Kinetoplast Division Factors in a Trypanosome. Issue 2 (February 2019) - Mensa-Wilmot, Kojo; Hoffman, Benjamin; Wiedeman, Justin; Sullenberger, Catherine; Sharma, Amrita
Abstract : Inheritance of the single mitochondrial nucleoid (kinetoplast) in the trypanosome requires numerous proteins, many of whose precise roles are unclear. By considering kinetoplast DNA (kDNA) as a template for cleavage into two equal-size networks, we predicted sets of mutant kinetoplasts associated with defects in each of the five steps in the kinetoplast cycle. Comparison of these kinetoplasts with those obtained after gene knockdowns enabled assignment of proteins to five classes – kDNA synthesis, site of scission selection, scission, separation, and partitioning. These studies highlight how analysis of mutant kinetoplast phenotypes may be used to predict functional categories of proteins involved in the biogenesis of kinetoplasts. Highlights: Kinetoplasts (mitochondrial genome nucleoids) are important in bloodstream trypanosomes for the establishment of mitochondrial membrane potential. Many proteins involved in segregation of kinetoplasts have been identified. A region between a kinetoplast and basal bodies is described as a tripartite attachment complex (TAC). A set of TAC-associated proteins (TACAPs) has been proposed as the machinery for kinetoplast segregation. Subcomplexes of TACAPs that form in vivo have been described. Several proteins that do not associate with TAC are involved in the maintenance of the kinetoplast. New kinetoplast-associated proteins have been identified. We are approaching an exciting period in the field when a molecular understanding of how all aspects of kinetoplast biogenesis are executed seems achievable.